Characterization of glucocorticoid-induced loss of DNA methylation of the stress-response gene Fkbp5 in neuronal cells. Issue 12 (2nd December 2021) - Cox, Olivia H.; Song, Ha Young; Garrison-Desany, Henri M.; Gadiwalla, Nuriya; Carey, Jenny L.; Menzies, Julia; Lee, Richard S.
ABSTRACT: Exposure to stress or glucocorticoids (GCs) is associated with epigenetic and transcriptional changes in genes that either mediate or are targets of GC signalling. FKBP5 (FK506 binding protein 5) is one such gene that also plays a central role in negative feedback regulation of GC signalling and several stress-related psychiatric disorders. In this study, we sought to examine how the mouse Fkbp5 gene is regulated in a neuronal context and identify requisite factors that can mediate the epigenetic sequelae of excess GC exposure. Mice treated with GCs were used to establish the widespread changes in DNA methylation (DNAm) and expression of Fkbp5 across four brain regions. Then two cell lines were used to test the persistence, decay, and functional significance of GC-induced methylation changes near two GC response elements (GREs) in the fifth intron of Fkbp5 . We also tested the involvement of DNMT1, cell proliferation, and MeCP2 in mediating the effect of GCs on DNAm and gene activation. DNAm changes at some CpGs persist while others decay, and reduced methylation states are associated with a more robust transcriptional response. Importantly, the ability to undergo GC-induced DNAm loss is tied to DNMT1 function during cell division. Further, GC-induced DNAm loss is associated with reduced binding of MeCP2 at intron 5 and a physical interaction between the fifth intron and promoter of Fkbp5 . Our results highlight several key factors at the Fkbp5 locus that may have important implications for GC- or stress-exposure during early stages of neurodevelopment.